Navigating the Singapore’s private international rules in the age of innovative cross-border commercial litigation framework - YIP, Man (Institutional Knowledge at Singapore Management University, 2018)
In the last decade, Singapore has been consistently working on consolidating its position as a leading dispute resolution hub in Asia. China’s One Belt One Road (OBOR) initiative affords, in principle, an invaluable opportunity for Singapore to foster its role in dispute resolution services. Conversely, the success of the OBOR is in part dependent upon the availability of reliable and efficient dispute resolution mechanisms to handle commercial disputes that will invariably arise. Singapore looks poised to contribute to the success of the OBOR in that respect, in light of its mature and business-friendly legal system. Coincidentally, China announced its OBOR in 2013 – the same year that the Chief Justice of the Singapore Supreme Court mooted his idea to create an innovative ‘international’ court, the Singapore International Commercial Court (SICC), to handle an expected increase in international commercial disputes in the region. In January 2015, following a series of consultations, the SICC was launched. In 2016, to increase the portability of its judgments abroad, Singapore signed on to the Hague Convention on Choice of Court Agreements 2005 (the ‘HCCCA’) and the Convention was given effect by way of local legislation in October the same year. However, these recent developments have also made Singapore courts’ jurisdictional framework as well as the rules on enforcement of foreign judgments far more complex than before. Prospective users of the Singapore dispute resolution services will need to consider their contractual arrangements and post-dispute strategy more carefully in order to achieve their desired objectives. This chapter suggests that the challenge posed by Singapore private international law rules is not that they are underdeveloped to deal with the likely increase in disputes in the region, which may be the more commonly encountered problem in other countries. To the contrary, the challenge is one of navigating the web of sophisticated, and in some respect, innovative rules. The chapter focuses on three main areas: the complex jurisdictional framework of the Singapore High Court (of which the SICC is a division), the enforcement of foreign judgments in Singapore as well as drafting of choice of court and choice of law clauses. The analysis shall highlight the areas of complexity, potential uncertainties and the drafting considerations that prospective users of Singapore litigation services must take on board. The chapter concludes that the challenge is not insurmountable and Singapore’s framework may inspire greater legal collaboration across the jurisdictions, as economic collaboration and integration take place through the OBOR.